Prevalence of Pelvic Floor Disorders in Female CrossFit Athletes. Issue 8 (August 2020) - High, Rachel; Thai, Kim; Virani, Hina; Kuehl, Thomas; Danford, Jill
Abstract : Objectives: This study aimed to estimate the prevalence of pelvic floor disorders by symptoms in female CrossFit athletes in the United States and characterize subjects reporting pelvic organ prolapse symptoms, urinary incontinence, and fecal incontinence. Methods: A 27-question anonymous questionnaire was distributed to owners of CrossFit-affiliated gyms. Select questions from validated questionnaires were used to define symptoms. Positive responses with "moderate, or quite a bit" bother defined the presence of urinary incontinence (with stress or urgency). A response of "yes" to "having a bulge or something falling out" defined the presence of pelvic organ prolapse. A response of "yes" to "lose stool beyond your control" questions defined the presence of fecal incontinence. Results: Three hundred fourteen respondents had mean age of 36 ± 10 years and a mean body mass index of 25.2 ± 4 kg/m 2 . Forty-four percent reported ≥1 vaginal delivery. For each workout, respondents reported lifting mean weights of 91 to 217 lb, and 90% reported participation in ≥3 CrossFit workouts per week. Pelvic floor disorder symptoms reported included the following: pelvic organ prolapse, 3.2% (10/314); urinary incontinence, 26.1% (82/314); and fecal incontinence, 6% (19/314). Higher age, parity, and number of vaginal deliveries were associated with urinary incontinence. Higher parity and number of vaginal deliveries were associated with prolapse. Fecal incontinence was not associated with age, body mass index, or obstetric history. Conclusion: The prevalence of pelvic floor symptoms in female CrossFit athletes from the general population is likely similar to the general population; however, the prevalence of bothersome urinary incontinence is higher than the general population in women younger than 40 years.